PENGARUH GPM, DER DAN EPS TERHADAP HARGA SAHAM PADA PT. ADHI KARYA (PERSEROAN), TBK YANG TERCATAT DI BURSA EFEK INDONESIA - Sanjaya, Rudi (RJABM (Research Journal of Accounting and Business Management), 2022)
The purpose of this study was to analyze the effect of Gross Profit Margin, Debt to Equity Ratio and Earning Per Share on stock prices at PT Adhi Karya Tbk period 2013-2020. The data collection method used in this study is secondary data. The type of data used in writing this thesis is quantitative data, namely the financial statements of PT Adhi Karya Tbk period 2013-2020. Financial statement management uses IMB SPSS version 22. The data analysis methods used in this research are financial ratio analysis, descriptive analysis, classical assumption test, model feasibility test, and causality effect test. From the results of the study it can be concluded that GPM (X1) partially has a significant effect on stock prices (Y), while DER (X2) and EPS (X3) partially have no significant effect on stock prices (Y). From the results of the F test, GPM, DER and EPS simultaneously have a significant effect on stock prices. And based on the coefficient of determination test shows a value of 0.727 which explains that GPM, DER and EPS affect stock prices by 72.7% while the remaining 27.3% is influenced by other factors not examined in this study.